1992
DOI: 10.1097/00000658-199201000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Choledochal Dilatation With Emphasis on Pathophysiology of the Biliary Tract

Abstract: Of 37 patients with congenital choledochal dilatation, aged 8 days to 12 years, who had undergone excision with Roux-en-Y hepaticojejunostomy, 26 patients could be analyzed for morphologic abnormalities and pathophysiology of the biliary tract. Of the 26 patients with congenital choledochal dilatation, 25 (96.2%) had an abnormal choledochopancreaticoductal junction. Of the 12 patients with cystic-type choledochal dilatation, 10 had the C-P type of abnormal choledochopancreaticoductal junction, and of the 13 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
16

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 4 publications
1
73
0
16
Order By: Relevance
“…Consequent chemical and enzymatic destruction of the duct wall leads to cystic dilation [17,18] . Iwai [19] and other authors [16,18] found that the choledochal dilation has a close association with abnormal choledochopancreaticoductal junction, whether direct or indirect. CT can clearly visualize cyst location, number, scope, stone and relationships with surrounding structures.…”
Section: Discussion Diagnosismentioning
confidence: 93%
“…Consequent chemical and enzymatic destruction of the duct wall leads to cystic dilation [17,18] . Iwai [19] and other authors [16,18] found that the choledochal dilation has a close association with abnormal choledochopancreaticoductal junction, whether direct or indirect. CT can clearly visualize cyst location, number, scope, stone and relationships with surrounding structures.…”
Section: Discussion Diagnosismentioning
confidence: 93%
“…[18][19][20][21] Many doctors believe that choledochal cyst in older children results from an anomalous insertion of the distal CBD into the pancreatic duct of Wirsung that permits reflux of pancreatic juice into the biliary tree, resulting in cholangitis, which weakens the bile duct wall and leads to cyst formation. 8,21 It has also been suggested that, in infancy, choledochal cyst and BA are part of the spectrum of infantile obstructive cholangiopathy and may be found concurrently in this stage of life. 22 A survey of the American Academy of Pediatric Surgery Section found that 13% of patients with cystic dilatation of the CBD had extrahepatic atresia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, various biliary cancer models were established, that investigate the initiating mechanisms involved in biliary carcinogenesis. Such experimental and clinical tumor models are the liver fluke infection with Opisthorchis viverrini (OV) [2][3][4], models of anomalous arrangement of the pancreaticobiliary ducts (APBD) and bilioenterostomy [5,6], clinical series of patients with congenital bile duct cysts (CBDC) and pancreaticobiliary maljunctions (PBM) [7][8][9] and tumor induction models that use chemical hepatobiliary carcinogens such as N-nitrosobis(2-oxopropyl)amine (BOP) [6,10] or diethylnitrosamine (DEN) [11]. With the introduction of translational research methods (e.g.…”
Section: Introductionmentioning
confidence: 99%